Giant Ovarian Mucinous Cystadenoma in Derna, Libya - Srgewa, Amal; Raffalla, Noria; Eljazwi, Naima; Sargewa, Essa (AlQalam Journal of Medical and Applied Sciences, 2024)
Giant mucinous cystadenomas of the ovary are seldom documented in literature within developed countries, primarily due to the widespread availability of diagnostic technologies. However, in developing nations, such situations pose a challenge owing to limited access to diagnostic tools and constrained resources. Herein, we present the case of 35-year-old women, who reported a three-year history of a progressively enlarging giant mucinous cystadenoma which was initially mistaken for obesity, accompanied by abdominal distension and pain, and was not diagnosed during the cesarean section performed three weeks prior to the significant increase in size. Cystectomy performed, the resected cyst measured 25x23x17 cm, with no evidence of ascites. Subsequent histopathological analysis confirmed the diagnosis of mucinous cystadenoma. The patient experienced a complete postoperative recovery without any complications. Notably, the presence of vague gastrointestinal symptoms unrelated to the actual diagnosis underscores the importance of considering giant ovarian cysts as a potential differential diagnosis for ambiguous abdominal symptoms, given the varied clinical presentations they may manifest. This case underscores the necessity for multidisciplinary collaboration among various specialists to facilitate early diagnosis. Furthermore, it emphasizes the indispensable role of histopathological examination in ensuring accurate diagnosis and appropriate management of ovarian cysts. اورام المبيض العملاقة نادرة الحدوث في البلدان المتقدمة، نظرًا لتوفر التقنيات التشخيصية الواسعة الانتشار. ومع ذلك، في الدول النامية، تشكل مثل هذه الحالات تحديًا بسبب الوصول المحدود إلى الأدوات التشخيصية والموارد المقيدة. هنا، نقدم حالة سيدة تبلغ من العمر 35 عامًا، والتي أبلغت عن تاريخ يمتد على مدى ثلاث سنوات من ورم مبيض عملاق متزايد تدريجيًا والذي كان معتبرا كسمنة، وكان مصحوبا بانتفاخ في البطن وألم ولم يتم تشخيصه اثناء العملية القيصرية التي سبقت ازدياد حجمه المفاجئ بثلاث اسابيع. أجريت عملية استئصال الكيس، وقياس الكيس المستأصل بأبعاد 25 × 23 × 17 سم، دون وجود أدلة على التجمع السائل في البطن. أكد التحليل النسيجي التشخيص انه ورم غدي كيسي بالمبيض. خلال فترة النقاهة بعد الجراحة، تعافت المريضة تمامًا دون حدوث أي مضاعفات. وجود أعراض هضمية غامضة غير متعلقة بالتشخيص الفعلي يؤكد على أهمية النظر في الأورام المبيضية العملاقة كتشخيص تفاضلي محتمل لأعراض البطن الغامضة، نظرًا لتنوع العروض السريرية التي قد تظهر بها. تؤكد هذه الحالة على ضرورة التعاون بين مختلف الاختصاصات لتسهيل التشخيص المبكر. علاوة على ذلك، فإنها تؤكد على الدور اللازم للفحص النسيجي لضمان التشخيص الدقيق والعلاج المناسب للأورام المبيضية.